The Tolerance of Ambiguity in the Virtual Identity Statuses among Student Users of Online Platforms - M.V. Klementyeva (Социальная психология и общество)
Objective. Assessment the contribution of virtual identity statuses and identity components to variation in uncertainty tolerance of ambiguity among users of online platforms in age of students. Background. The users of online platforms reconsider identity commitments and explore identity alternatives in conditions of information uncertainty and ambiguity. Previous studies have clearly established what non-adaptive processes of identity development in real environments compensating for by problematic use of online platforms and assessing with low levels of tolerance for uncertainty, but little is known about the impact of virtual identity on tolerance of ambiguity. Study design. We how ambiguity tolerance relates to virtual identity using a survey method among students who are users of online platforms. The associations of virtual identity and tolerance of ambiguity were examined using Pearson's r-test, and linear regression (Fisher's F-test), and structural equation modeling (SEM). Participants. The sample consisted of data obtained from 350 students (35% male; 65% female), aged 18 to 25 (M = 19,8; SD = 1,62), users of online platforms. Measurements. The study measured the indicators of virtual identity (VISI) and tolerance of ambiguity (MSTAT-I) using methods adapted to the Russian research pool. Results. Commitment of virtual identity increases tolerance of ambiguity – a general measure, uncertainty preference, of attitudes towards new, ambiguous, difficult to understand, uncertain and internally contradictory environmental stimuli. The Exploration of virtual identity is associated with a preference for uncertainty. We have found that age raised the levels of the understanding of complex information and reduces the levels of the interest in new stimuli decreases. The outcomes of this study revealed that age gradient was found to be more pronounced in males than females, such that users of the males demonstrated higher growth forecast of levels of a tolerance of ambiguity. Moreover, a virtual identity status influences tolerance for ambiguity, such that users with a diffuse virtual identity reported a tendency to perceive ambiguity (ambiguous and new) situations as sources of threat. Conclusions. The current study sparse existing literature of psychology with new data of whether tolerance of ambiguity relates robustly to identity, and support predictions of variability in tolerance of ambiguity depending on the virtual identity status, age and gender among users of online platforms in age of students. The pre-adaptive mechanism that links components of identity search and acceptance in virtual environments use to tolerance of ambiguity, this mechanism may be further moderated by age and gender factors.